Karakteristik Nilai CBR California Bearing Ratio Dan Permeabilitas Pada Tanah Lempung Dengan Penambahan Renolith Dan Fly Ash - Samaa, Rifka Kendek; Sariman , Syahrul; Setiawan, Arman (Program Studi Teknik Sipil Universitas Bosowa, 2024)
Soil consists of relatively weak bonds between particles, often caused by carbonates, organic matter, or oxides that settle between the particles. As a construction foundation, soil sometimes does not meet the required specifications, such as clay, which has many limitations when used as a subgrade. Chemical additives can be used for soil reinforcement, such as Renolith and Fly Ash. In this study, each sample was substituted with 3% Renolith, along with Fly Ash additions of 10%, 15%, and 20%. For the California Bearing Ratio (CBR) test, three original soil samples were used, with an original CBR value of 25.38%. This value increased to 31.03% with the addition of 3% Renolith and 0% Fly Ash, showing that Renolith enhances CBR, with further increases seen with 3% Renolith plus 10%, 15%, and 20% Fly Ash. For permeability testing, one original soil sample was used, with each composition variation weighing 500 grams. The permeability coefficient of the original soil was 0.0017%, which increased to 0.0039% with 3% Renolith and 0% Fly Ash. This demonstrates that Renolith improves permeability, with further increases achieved by adding 3% Renolith plus 10%, 15%, and 20% Fly Ash. Using Renolith and Fly Ash can enhance the CBR and permeability coefficients, improving the load-bearing capacity of clay soil.